2016
DOI: 10.3184/146867816x14720534560565
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on the Kinetics and Mechanism of the Synthesis of Fluorescent 3,8-Disubstituted-3H-Imidazo [4,5-a] Acridine-11-Carbonitriles

Abstract: 3,8-Disubstituted-3H-imidazo[4,5-a]acridine-11-carbonitriles show very interesting optical properties. In some cases, they have higher quantum yields compared to well-known fluorescent dyes such as fluorescein. Hitherto, no detailed theoretical study has been reported on the mechanism of the synthesis of the titled compounds, hence an accurate and detailed theoretical investigation on the synthesis of these dyes is desirable. In this paper, density functional theory (DFT) methods have been employed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Recently, we performed DFT calculations using the B3LYP hybrid functional and the 6-311++G(d,p) basis set to gain the most reasonable mechanism for the formation of 3H-imidazo [4,5-a]acridines. 28 The results obtained revealed that intramolecular electrophilic aromatic substitution is the most likely mechanism for cyclisation of the intermediate in these reactions. According to these results, 28 the most plausible reaction mechanism to explain the formation of fluorophores 3a-d involves the attack of the anion derived from 2 on compounds 1a-d and the generation of intermediates A and A′ followed by dehydration of A′′ and the formation of intermediate B in basic media, as depicted in Scheme 2.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, we performed DFT calculations using the B3LYP hybrid functional and the 6-311++G(d,p) basis set to gain the most reasonable mechanism for the formation of 3H-imidazo [4,5-a]acridines. 28 The results obtained revealed that intramolecular electrophilic aromatic substitution is the most likely mechanism for cyclisation of the intermediate in these reactions. According to these results, 28 the most plausible reaction mechanism to explain the formation of fluorophores 3a-d involves the attack of the anion derived from 2 on compounds 1a-d and the generation of intermediates A and A′ followed by dehydration of A′′ and the formation of intermediate B in basic media, as depicted in Scheme 2.…”
Section: Resultsmentioning
confidence: 89%
“…28 The results obtained revealed that intramolecular electrophilic aromatic substitution is the most likely mechanism for cyclisation of the intermediate in these reactions. According to these results, 28 the most plausible reaction mechanism to explain the formation of fluorophores 3a-d involves the attack of the anion derived from 2 on compounds 1a-d and the generation of intermediates A and A′ followed by dehydration of A′′ and the formation of intermediate B in basic media, as depicted in Scheme 2. Finally, intramolecular electrophilic aromatic substitution of C to D led to the formation of the compounds 3a-d.…”
Section: Resultsmentioning
confidence: 89%
“…As depicted in Scheme 2, the mechanism behind the preparation of the novel 3a ‐ e can be considered to be as follows 43 . The attack of the anion 2 on the compounds 1a‐e produces the intermediates A and A′ followed by the dehydration of A″ and the preparation of intermediate B in alkaline solution.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the photoelectrochemical measurements can be found in our earlier studies 42,43 . As represented in Figures 5 and 6, the I ‐ V curves and the IPCE spectra of the heterocyclic compounds 3a‐e have been subjected to investigation.…”
Section: Resultsmentioning
confidence: 99%